PENGARUH KOMITMEN ORGANISASIONAL, KOMITMEN PROFESIONAL, MOTIVASI KERJA, KONFLIK PERAN, KETIDAKJELASAN PERAN DAN KELEBIHAN PERAN TERHADAP KEPUASAN KERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI PEKANBARU, PADANG DAN BATAM - Edwy, Ferby Mutia; Ratnawati, Vince; Haryani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the effect of organitational commitment, professional commitment, motivation to work, role conflict, role ambiguity and role overload on auditor’s satisfication. This research conducted in Pekanbaru, Padangand Batam. The respondents are auditors who work at public accountant office according to directory of IAPI. The sampling technic using total sampling. Data was collected by questionnaire delivered directly. 119 questionnaire was distributed, but only 87 questionnaire were returned. Data were analyzed using multiple linear regression analysis with SPSS version 20.00. The result showed that organitational commitment, professional commitment, motivation to work, role ambiguity and role overload variables have significant influence on auditor’ssatisfication, but role conflict variable does not have significant influence on auditor’s satisfication. The coefficient of determination shows that the effect of organitational commitment, professional commitment, motivation to work, roleconflict, role ambiguity and role overload on auditor’s satisfication amounted to 64.1%.Keywords: Commitment, Motivation, Role, Work Satisfication